Study of Correlation Between Length of Ulna and Body Height Among Delta State University Students in Nigeria - Udi, OA; Godswill, Okoro Ogheneyebrorue; Ovie, H; Ozoko, LE Chris (International Journal of Human and Health Sciences (IJHHS), 2022)
Background:The height of an individual is one of the most important parameters contributing greatly to the process of identification of a person from their skeletal remains and it is dependent greatly on the age, race, gender, body composition and nutrition of the person. Objective: The study aims to correlate between body height and subcutaneous ulnar length among Delta State University students and to see if any difference exists between right and left ulnar lengths. Methods: A total of 240(105males and 135females) studentsfrom Delta State University, Abraka, Delta State, Nigeria,aged between 20 and 33 years, without any known disability participated in this study. Results:The mean age was22.81±2.43. The mean body height and ulna length of adult male were significantly higher than the adult females. Positive correlation was found between total body height and ulna length of 0.50. Conclusion:Our data suggest a definitive and strong correlation between the body height and ulnar length. International Journal of Human and Health Sciences Vol. 06 No. 03 July’22 Page: 309-312